Weefkuns in Suider-Afrika met besondere verwysing na tapyte en tapisseriee - Nilant, F.G.E. (Felix Gottlieb Ernst) (University of Pretoria, 2022)
Dissertation (MA (Art History and Fine Arts))--University of Pretoria, 1979.